Identification of a new neonatal population at risk using the Peruvian fetal growth curve - Ticona Rendón, Manuel (2015)
OBJECTIVE: To determine small for gestational age (SGA) newborns when using the Peruvian intrauterine growth curves and to study their risk for morbidity and mortality. DESIGN:Prospective, analytical, case-control study. SETTING:Peruvian Ministry of Health hospitals. PARTICIPANTS: Live newborns. INTERVENTIONS: Ninety-five thousand seven hundred and fifty-one neonates from 29 Peruvian Ministry of Health hospitals born during 2005 were classified by applying both Lubchenco and Peruvian weight intrauterine growth curves. Percentage distribution was compared and significant differences was considered when p < 0,05. We studied additional SGA (named new SGA) newborns risks for morbidity and mortality in comparison with adequate for gestational age (AGA) newborns, from week 37 through 42, using odds ratio with 95% confidence interval. Perinatal System Informatic Data was used. MAIN OUTCOME MEASURES: Percentage of adequate, large and small for gestational age newborns; ‘new’ SGA’ risks. RESULTS: Large for gestational age (LGA) newborns diminished significantly from 14,3% to 11,4%, AGA decreased from 81,7% to 78,5%, and SGA newborns increased from 4,1% to 10,1%. There were 9664 SGA newborns when using the Peruvian curve and 3 899 when using Lubchenco’s. The difference of 5 765 newborns (6% of the whole population) corresponds to the ‘new’ SGA newborns that presented the following risks: neonatal mortality (OR = 15,6), metabolic dysfunction (OR = 2,2), congenital malformations (OR = 2,1), infections (OR = 2), respiratory distress syndrome, (OR = 1,8) perinatal asphyxia (OR = 1,7) and neonatal morbidity (OR = 1,5). CONCLUSIONS: Lubchenco’s curve overestimates LGA newborns and underestimates SGA newborns, and as such is not a demanding standard for Peruvian newborns. The new SGA group had high morbidity and mortality risk.